Genome size stability across Eurasian Chenopodium species (Amaranthaceae). (5th October 2016) - Vít, Petr; Krak, Karol; Trávníček, Pavel; Douda, Jan; Lomonosova, Maria N.; Mandák, Bohumil
Abstract : Tremendous interspecific genome size variation is a well known phenomenon, whereas genome size within a species is supposed to be exceptionally stable and thus useful as a taxonomic trait. Using DAPI flow cytometry, we tested the stability of genome size in various representatives of Chenopodium s.s . (Amaranthaceae) across a broad geographical range (from Portugal to eastern Russia) in Eurasia. We sampled 1977 Chenopodium individuals of four different ploidies (di‐, tetra‐, hexa‐ and decaploids) from 347 populations. Intraspecific relative genome size variation was low, ranging from 2.0% in C . probstii to 7.7% in C . album, even in the species with broad distributions. We distinguished 12 homogeneous relative genome size groups among the 17 Chenopodium spp. tested. Genome size is useful for distinguishing certain morphologically similar groups of species such as C. suecicum / C. album, C . vulvaria / C . pamiricum – C . iljinii / C . sosnowskyi / C . karoi . Due to its genome size stability, the cosmopolitan species C . album can be used as an alternative internal standard in flow‐cytometric analyses with the additional advantages of annual life cycle, self‐compatibility and common occurrence all over the world. Finally, we did not detect any sign of hybridization between Chenopodium spp. of different ploidies.